In-vitro susceptibility of wound bacteria of domestic carnivores to different mixtures of honey and Nigella sativa L. seed extracts - Derbal Saïd; Niar Abdellatif; Hanfer Mourad (International Journal of Veterinary Science and Research - Peertechz Publications, 2019)
The aim of this study is to evaluate the bactericidal activity of honey alone and honey mixed with different Nigella sativa L. seed extracts against bacterial isolates from chronic wounds of domestic carnivores. The preparation of Nigella sativa L. seed extracts was carried out by macerating the seed powder in increasingly polar solvents (ethyl acetate, ethanol and methanol). The study of the minimum bactericidal concentration of honey alone and honey mixed with different Nigella sativa L. seed extracts was carried out by Broth Dilution Method. The results showed that the addition of different Nigella sativa L. seed extracts decreased the bactericidal activity of honey against Escherichia coli and potentiated this bactericidal activity against Staphylococcus intermedius. Ethanolic and ethyl acetate extracts of Nigella sativa L. seeds did not influence the bactericidal activity of honey against Staphylococcus aureus and Enterococcus faecalis. Addition of different Nigella sativa L. seed extracts showed a variable influence on the bactericidal activity of honey against Enterobacter sp.. Methanolic extract of Nigella sativa L. seeds potentiated the bactericidal activity of honey against Staphylococcus aureus, Staphylococcus intermedius, Enterococcus faecalis and Enterobacter sp.. These results revealed that combinations of methanolic extract of Nigella sativa L. seeds with honey can be used for the development of potent antibacterial dressing.